A semantic analysis of clickbait news headlines on Malaysian alternative online news portals - Chen, Jia Yee (2024)
The expanding realm of online media has provided fertile ground for the proliferation of clickbait techniques within the Malaysian media landscape. This paper is an investigation into the mechanics of clickbait headlines on Malaysian alternative news portals: World of Buzz, SAYS, and Free Malaysia Today using Biyani et al. (2016) and Pujahari and Sisodia (2020)’s Clickbait Categorization Framework. 30 clickbait headlines from articles published between January 2019 and December 2023 were selected, compiled, and semantically analyzed to identify recurring and prevalent patterns of linguistic features. The research findings reported that all headlines exhibit traits of multiple types simultaneously, and that “Teasing and Ambiguous” are the most common pairing identified. All other identified combined categories also originate from this foundational combination. It was also found that clickbait headlines are more prevalent in soft news compared to hard news. Moreover, findings conclude that the five main features of clickbait headlines, as deduced from this research, include (1) the use of the direct address technique, (2) integration of listicles, (3) dependance on emotional appeal, (4) utilization of rhetorical questions and (5) the application of capitalization. The implications of this study underscore the dynamic composition of clickbait headlines by local journalists, revealing both differences and similarities in writing styles between them and those from foreign countries. This enhances comprehension regarding the linguistic features used and the semantic relationship among these features in aiding the writers to convey the intended message and to entice readers to engage with the full article.